ยางบวมน้ำจากยางธรรมชาติอิพอกไซด์และพอลิเมอร์ดูดซึมน้ำได้มาก Water Swellable Rubber from Epoxidized Natural Rubber and Superabsorbent Polymer - วัดจัง, ชัยวุฒิ; บุญสิงห์, ศศิวงศ์; คำสอน, ธนากร; ประเสริฐศรี, สราวุธ (Science Essence Journal, 2016)
บทคัดย่อ งานวิจัยนี้ศึกษาผลของปริมาณพอลิเมอร์ดูดซึมน้ำได้มาก (SAP) และพอลิเอทธิลีนไกลคอล (PEG) ที่มีผลต่อสมบัติเชิงกลของยางบวมน้ำ (WSR) ที่เตรียมจากยางธรรมชาติอิพอกไซด์ (ENR) โดยบดผสมยาง ENR กับ SAP และสารเคมีอื่นๆ ด้วยเครื่องผสมระบบปิดและเครื่องผสมสองลูกกลิ้ง โดยตัวแปรที่ศึกษาคือ ปริมาณของ PEG และ SAP ที่มีต่อสมบัติการคงรูป ความทนทานต่อแรงดึง ระยะยืด ณ จุดขาด ความแข็ง การเสียรูปหลังการกด การบวมพองและการขยายตัวในน้ำของ ENR/SAP WSR ผลการศึกษาพบว่า การเพิ่มปริมาณ PEG ส่งผลทำให้สมบัติแรงบิดต่ำสุด แรงบิดสูงสุด และผลต่างของแรงบิดมีแนวโน้มลดลง แต่ไม่มีผลต่อระยะเวลาเริ่มเกิดการคงรูปและเวลาในการคงรูปของยางคอมปาวด์ ENR/SAP WSR นอกจากนี้การเติม PEG ช่วยให้สมบัติการทนทานต่อแรงดึงและระยะยืด ณ จุดขาด ของ ENR/SAP WSR ดีขึ้น แต่ทว่าการเพิ่มขึ้นของ PEG ช่วยให้การดูดซึมน้ำและการขยายตัวในน้ำให้กับ ENR/SAP WSR เพิ่มขึ้นเพียงเล็กน้อย ในขณะที่การเพิ่มปริมาณ SAP ช่วยให้การบวมพองน้ำและการขยายตัวในน้ำของ ENR/SAP WSR สูงขึ้น โดยปริมาณ SAP ที่ 50 phr ให้การบวมพองที่ 274% และการขยายตัวในน้ำที่ 376% แต่อย่างไรก็ตามการเพิ่มปริมาณ SAP กลับส่งผลให้สมบัติเชิงกลของ ENR/SAP WSR ด้อยลง ABSTRACT This research studied the effects of superabsorbent polymer (SAP) and polyethylene glycol (PEG) content on the properties of water swellable rubber (WSR) prepared from epoxidized natural rubber (ENR). ENR was mixed with SAP and other ingredients by using internal mixer and two-roll mill. The effects of PEG and SAP contents on cure properties, tensile strength, elongation at break, hardness, compression set, water swelling and water expansion of ENR/SAP WSR were focused. The results showed that minimum torque (ML), maximum torque (MH) and the torque different (MH-ML) of ENR/SAP WSR rubber compound trended to decrease with increasing PEG content, while scorch time and cure time of ENR/SAP WSR rubber compound were not affected. Additionally, tensile strength and elongation at break of ENR/SAP WSR were improved by incorporation of PEG. However, the water swelling and water expansion of ENR/SAP WSR slightly increased with increasing PEG content. On the other hand, the increasing of SAP contents raised the water swelling and water expansion of ENR/SAP WSR. The maximum of water swelling and water expansion was ca. 274 % and 376 %, respectively, at 50 phr of SAP. However, increasing the SAP content caused a decrease in mechanical properties of ENR/SAP WSR.